Kinematic correlates of early speech motor changes in cognitively intact APOE-ε4 carriers: a preliminary study using a color-word interference task - Dadgostar, Mehrdad; Hanford, Lindsay C.; Green, Jordan R.; Richburg, Brian D.; Cannon, Averi Taylor; Barnett, Nelson V.; Salat, David H.; Arnold, Steven E.; Eshghi, Marziye (Frontiers in Neurology, 2025)
IntroductionAlzheimer’s disease (AD) is the most prevalent form of dementia and a major public health challenge. In the absence of a cure, accurate and innovative early diagnostic methods are essential for proactive life and healthcare planning. Speech metrics have shown promising potential for identifying individuals with mild cognitive impairment (MCI) and AD, prompting investigation into whether speech motor features can detect elevated risk even prior to cognitive decline. This preliminary study examined whether speech kinematic features measured during a color-word interference task could distinguish cognitively normal APOE-ε4 carriers (ε4+) from non-carriers (ε4−).MethodsSixteen cognitively normal older adults (n = 9 ε4+, n = 7 ε4−) completed a sentence-based color–word interference task while three-dimensional electromagnetic articulography recorded lower-lip movements. Lip movement duration (s), average speed (mm/s), and range of movement (mm³) were extracted for three sentence segments: pre-interference, during-interference, and post-interference. Difference measures (ΔDuring–Pre, ΔDuring–Post) were computed to quantify task-related modulation. Descriptive statistics and independent t-tests were used to examine group-level trends. For classification, a support vector machine (SVM) with a degree-2 polynomial kernel and leave-one-out cross-validation evaluated all feature combinations derived from the 15 kinematic measures.ResultsAlthough no group differences reached statistical significance after accounting for multiple testing, several features showed moderate effect sizes. The optimal SVM model achieved 87.5% cross-validated accuracy (precision 88.9%, sensitivity 88.9%, specificity 85.7%) using three features: (1) lip movement duration during the pre-interference segment, (2) average lip speed during interference, and (3) the change in lip movement range from pre- to during-interference segments (ΔDuring–Pre).DiscussionThese findings suggest that lip kinematic responses to mild cognitive–motor interference may capture subtle neuromotor differences associated with APOE-ε4 status in cognitively intact older adults. The identified features point to potential alterations in anticipatory motor planning, interference susceptibility, and articulatory adaptability in ε4+ individuals. However, the small sample size, risk of overfitting, and sex imbalance limit interpretability. Thus, these results should be viewed as hypothesis-generating. Larger, sex-balanced, and longitudinal studies are needed to validate these candidate markers and clarify their role in multimodal early AD risk stratification.